Gambaran Maloklusi dan Tingkat Kebutuhan Perawatan Maloklusi Berdasarkan Occlusion Feature Index (OFI) pada Anak Penyandang Disabilitas di SLB Negeri Branjangan Kabupaten Jember - Irhamna Chairunnisa (Fakultas Kedokteran Gigi, 2025)
Children with Disabilities are at higher risk of experiencing malocclusion due to the limitations they have in maintaining oral hygiene. Branjangan State Special School in Jember Regency is one of the special schools with the most students with disabilities in Jember Regency, namely 145 students who do not receive services and counseling regarding dental and oral health, especially cases of malocclusion. Untreated malocclusion will have a negative impact on sufferers, so it is important to treat malocclusion. Until now, there has been no statistical data showing the picture of malocclusion and the level of need for malocclusion treatment in children with disabilities in Jember Regency. The purpose of this study was to examine the picture of malocclusion and the level of need for malocclusion treatment in children with disabilities at Branjangan State Special School in Jember Regency based on the Occlusion Feature Index (OFI). The type of research used in this study is descriptive observational with a purposive sampling technique and the sample size obtained that met the inclusion criteria was 15 children. The results of this study indicate that the severity and level of malocclusion treatment needs in children with disabilities at SLB Negeri Branjangan, Jember Regency based on OFI are, as many as 4 children (26.7%) with mild malocclusion and there is a slight variation from the ideal occlusion that does not need to be treated, 5 children (33.3%) with moderate malocclusion with indications for malocclusion treatment, 6 children (40%) with severe malocclusion who really need malocclusion treatment. From the data obtained, it can be concluded that as many as 73.3% of children with disabilities at SLB Negeri Branjangan, Jember Regency experience malocclusion that requires malocclusion treatment with the most categories being in the severe malocclusion category that really needs malocclusion treatment.
Reupload File Repository_Yudi :: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Children with Disabilities; Malocclusion and Need for Malocclusion Treatment; Occlusion Feature Index (OFI)